Pengaruh Variasi Penimbangan Terhadap Akurasi Penentuan Bilangan Asam Pada Alkyd Resin - Firman Adji Nur Hidayat; I Gusti Made Sanjaya (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2022)
- Alkyd resin is a modified polyester with the addition of fatty acids and other components. Alkyds are derived from polyols and organic acids including dicarboxylic acids or anhydrous carboxylic acids and triglyceride oils. The quality of an alkyd resin is determined based on its parameters including solid content, viscosity, acid number, color and clarity. High acid numbers can cause the paint to turn yellow easily, therefore accuracy is needed in analyzing acid numbers. To determine the acid number is done by acidimetric titration method. Products A, B, and C were weighed respectively: 0.5g, 2g, 4g, 6g, 8g, 10g, 12g, 14g, into a 300 ml erlenmeyer which already contained 100 ml of solvent. Enter the magnetic stirrer and stir until completely dissolved over the electric heater. Add 2 drops of 1% phenolphthalein indicator into the Erlenmeyer. Pour the 0.2 alcoholic KOH solution into a 50 ml burette. The titration was carried out until the solution changed from colorless to pink. Record the volume obtained (ml). From the research conducted, the smaller the sample being weighed, the larger the deviation from the analysis of the acid number from the theoretical weighing sample (10 grams). Based on the % accuracy allowed is 3%, the weighing variable that can be tolerated is 8–14 grams. Weighing samples less than 8 grams or above 14 grams will produce acid numbers which have very large deviations. Key words: Alkyd resin, Acid number, KOH solution, Titration